Analisis Penggunaan Mobile Banking pada Generasi Milenial dengan Pendekatan Technology Acceptance Model (TAM) - Mu’asiroh, Lutfi Rokhiyatul; Darwanto, Darwanto (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
This research aims to analyzeÂ the factors that can influence the millennial generation in usingÂ mobile banking. The approach in this research uses theÂ Technology Acceptance ModelÂ (TAM)Â that has been developed by Davis (1989), namely benefits and convenience, and by adding three external variables, namelyÂ security, experience and compatibilityÂ . The research model was empirically tested using survey data from the millennial generation of students at Diponegoro University. TheÂ result of the analysis shows that all constructs in the TAM model namelyÂ benefits, convenience and the three external variable, security, experience and compatibilityÂ have a positive and significant effect on theÂ use ofÂ mobile bankingÂ in the millennial generationÂ partially or simultaneously.Â The implication of the results of this research is relevant for the millennial generation to be more confident on usingÂ mobile banking thatÂ can simplify their banking activities.